PENTINGNYA PELAKASANAAN TIMBANG TERIMA DI RUANGAN PELAYANAN KEPERAWATAN - Ardi Wahyudi; Peri Linayani; Rini Apriani (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2022)
Abstract Background: Nursing services can run well if nursing managers can play a good role with the aim of providing services oriented to patient safety through effective communication. It is done through good handover communication as well. Objective: This study aimed to describe the importance of the implementation of handover the nursing service room. Methodology: This journal review method consists of various steps which include selecting topics to be studied, searching for literature sources, analyzing the literatures and the last stage is the process of writing into a scientific writing. Results: based on a review of the journal, it was found that there was a relationship between the leadership of the head of the room, the function of direction and supervision activities with weigh-in in the nursing service room. Policies related to monitoring and evaluation, as a good communication medium in consideration so that the implementation of SBAR communication can be carried out effectively. Peer support and knowledge support the success of the weigh-in. Weighing can improve patient safety. Conclusion: Weighing in is important in improving patient safety in nursing services. Suggestion: support, monitoring and evaluation on a regular basis so that communication between nurses at the time of weighing can be done through policies and SOPs available in the room as well as information dissemination programs related to weighing and receiving. Abstrak Latar belakang: Pelayanan keperawatan dapat berjalan dengan baik apabila manajer keperawatan dapat berperan dengan baik dengan tujuan pelayanan memberikan pelayanan berorientasi pada keselamatan pasien melalui komunikasi yang efektif. Hal ini dilakukan melalui komunikasi Timbang terima yang baik pula. Tujuan: mengetahui gambaran tentang petingnya pelakasanaan timbang terima di ruangan pelayanan keperawatan. Metodologi: Metode telaah jurnal ini terdiri dari berbagai langkah yang meliputi pemilihan topik untuk ditelaah, pencarian sumber literature, menganalisa sumber literature yang ditemukan dan tahap terakhir adalah proses menulis ke dalam sebuah penulisan ilmiah. Hasil: berdasarkan telaah jurnal didapatkan hasil adanya hubungan kepemimpinan kepala ruangan, fungsi pengarahan dan kegiatan supervisi dengan timbang terima di ruangan pelayanan keperawatan. Kebijakan terkait monitoring dan evaluasi, sebagai media komunikasi yang baik dalam timbang terima agar pelaksanaan komunikasi SBAR dapat dilakukan secara efektif. Dukungan teman sejawat dan pengetahuan mendukung keberhasilan timbang terima. Timbang terima dapat meningkatkan keselamatan pasien. Kesimpulan: Timbang terima penting dalam meningkatkan keselamatan pasien di pelayanan keperawatan. Saran: dukungan, monitoring serta evaluasi secara berkala agar komunikasi antar perawat pada saat timbang terima dapat dilakukan melalui kebijakan dan SPO yang tersedia di ruangan serta program diseminasi informasi terkait timbang terima.